Eksplorasi Hasta Karya dan Pengembangan Kreativitas Serta Motorik Anak Usia Dini Melalui Kegiatan Clay di Paud - Fauzan, Alfi Nura; Anggraini, Elya Siska; Mawarni, Rina; Duha, Yulenta; Zahiroh, Zalfa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
PAUD has an important role in forming the foundation of children's development, both physically, cognitively, linguistically, emotionally, and socially. Through various activities and learning that are packaged in a fun way, children are invited to develop social skills, emotional intelligence, creativity, and various other aspects of development. Creativity is the ability possessed by a person to produce a new/original idea/product that has utility value, where the results of the idea/product are obtained through the process of imaginative activities. The method used in this study is the qualitative research method. The purpose of this study is to explore further information and deepen understanding of obstacles or constraints in the development of children's creativity, as well as strategies for developing early childhood creativity. The results of the study indicate that the problem of the creativity aspect at RA Darussalam visited by the author is more dominant in the aspect of musical creativity than handicrafts. Therefore, the author suggests clay creations as a solution to the problems in this aspect.